A Cosmological Scenario from the Starobinsky Model within the f(R, T) Formalism. (2nd June 2019) - Moraes, P. H. R. S.; Sahoo, P. K.; Ribeiro, G.; Correa, R. A. C.
Abstract : In this paper we derive a novel cosmological model from thef ( R, T ) theory of gravitation, for whichR is the Ricci scalar andT is the trace of the energy-momentum tensor. We consider the functional formf ( R, T ) = f ( R ) + f ( T ), withf ( R ) being the Starobinsky Model, namedR + α R 2, andf ( T ) = 2 γ T, withα andγ being constants. We show that a hybrid expansion law form for the scale factor is a solution for the derived Friedmann-like equations. In this way, the model is able to predict both the decelerated and the accelerated regimes of expansion of the universe, with the transition redshift between these stages being in accordance with recent observations. We also apply the energy conditions to our material content solutions. Such an application makes us able to obtain the range of acceptability for the free parameters of the model, namedα andγ .